Integrating Sustainable Stormwater Management in Urban Planning: Ways Forward towards Institutional Change and Collaborative Action - Anna Bohman (Water, 2020)
Climate change impacts, ageing infrastructure and the increasing imperviousness of cities all raise enormous challenges to and call for new ways of planning for sustainable urban stormwater management. Especially, closer collaboration among a diverse set of actors involved has been pointed to as critical to enable the development of holistic and flexible approaches. However, the shift towards inclusive forms of planning has been slow, and characterized by technical and institutional lock-ins. Against this background, this study scrutinizes the challenges and developments perceived as central for improving stormwater planning, and analyzes how formal and informal institutional change could contribute to enhancing sustainability in this sector. Building on an analysis of data from workshops, interviews and a survey with Swedish planners and water managers, we suggest new strategies for integrating stormwater concerns into planning processes, overcoming silo structures, fostering cocreation cultures, and securing the continuation and implementation of stormwater management through various planning stages.